Proporsionalitas Pemidanaan Terhadap Tindak Pidana Kealpaan yang Menyebabkan Orang Lain Meninggal Dunia dan Luka- - Luka (Studi Putusan Pengadilan) - Fadhila Nur Amalia Afiffah; Ayu Izza Elvany (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
The judge's consideration is an important matter in imposing a sentence, so it is necessary to conduct a deeper review of the suitability between the amount of sentencing and the considerations used by judges, it is because the judge's considerations have a big influence on the proportionality of sentencing and determining the amount of sentencing. With this, it is hoped that the sentencing given can fulfill a sense of justice for all parties. This study aims to determine the factors considered by judges in imposing sentences and the proportionality of sentencing in cases of negligence that caused other people to die and to be injured. The type of research is descriptive normative juridical research with a research approach in the form of statiute approach and case approach. The results of the research show that judges in determining the factors used in their judgments are based on juridical and non-juridical considerations. Of the four existing decisions, there are 2 decisions that have not been proportional and 2 others have been proportional, this is because the determination of the proportionality of a decision is based on the level of seriousness of the crime committed by the Perpetrator.